Synthesis of hybrid myocardium constructs and in vitro characterization under mechanical stimulation. (December 2022) - Günal, Gülçin; Zihna, Gizem; Akel, Hayriye; Okan, Meltem; Karaaslan, Cagatay; Aydin, Halil Murat
Abstract: The myocardium tissue may lose its contraction and mechanical characteristics due to irreversible necrosis in cardiac muscles in patients with infarction history. The repair of such damages by the body is unfortunately not possible since the adult cardiomyocytes fail to divide themselves. Recently, stem cells, cell sheet technologies, decellularized and synthetically produced cardiac constructs for the regenerative solutions for such situations have been widely studied in cardiac tissue engineering. Within the scope of this study, Poly(glycerol-sebacate) (PGS) elastomer impregnated decellularized matrices (hybrid) were produced for the myocardium regeneration. Firstly, the effectiveness of the decellularization approach was investigated. Next, chemical, mechanical and morphological characterizations of the hybrid structures were studied. Young modulus values were found as 83.3 ± 22.6 kPa, 654.6 ± 16.7 kPa and 340.5 ± 17.8 kPa for native tissue, decellularized tissue and hybrid construct, respectively. The hybrid constructs were recellularized with human cardiomyocytes and mechanically stimulated using a bioreactor. Compared to static cell culture conditions, dynamic cell culture studies showed a remarkable cell proliferation rate up to the 14th day of the culture period. The applied mechanical stimulation improved the cell proliferation, increased the GAG amount and gene expressions for cardiac markers. Graphical Abstract: ga1 Highlights: Decellularization process causes a major loss of the tissue architecture. The extracellular matrix and Poly(glycerol-sebacate) polymer is combined to improve mechanical properties of cardiac patch. An alternative hybrid candidates as cardiac biomaterials for regenerative medicine.